Characteristics of the specific features of marketing in tourism - Shapoval, V. S.; Pererva, P. G. (Видавничий центр Київського національного університету культури і мистецтв, 2023)
It has been proven that the implementation of marketing research in the tourism industry has its own specificity, which is primarily related to the fact that tourism belongs to the service sector. If we compare marketing research in the field of services and in the field of the goods market, we will see that more complex methods are used in the first case.
Характеристика особливостей маркетингу в туризмі
Keywords: tourism business; marketing; demand; supply; competition; price policy